PENGARUH TRANSPARANSI DAN AKUNTABILITAS TERHADAP PENGUATAN EFEKTIVITAS TATA KELOLA APBDES UNTUK MEWUJUDKAN GOOD GOVERNANCE DI KECAMATAN WONOAYU, KABUPATEN SIDOARJO - Abdhilla, Indhira Ridho (LPPM Universitas Bina Bangsa, 2025)
This study investigates the influence of transparency and accountability on the effectiveness of Village Budget (APBDes) governance to achieve good governance principles in Wonoayu District, Sidoarjo Regency. A quantitative descriptive method was utilized in this research, and data were collected via questionnaires distributed to 99 village officials selected through purposive sampling. Multiple linear regression analysis was employed to evaluate the impact of the independent variables (transparency and accountability) on the dependent variable (effectiveness of APBDes governance). The results reveal that transparency significantly influences the effectiveness of APBDes governance by enhancing information openness and public participation. Conversely, accountability does not significantly affect the effectiveness of governance, indicating the need for additional factors such as external oversight and community involvement. These findings underscore the necessity of prioritizing transparency in village budget management while addressing gaps in accountability practices. This research contributes to the existing literature by highlighting the distinct roles of transparency and accountability in village financial governance.